Transforming Education: Case-Based Integrated Learning Development and Implementation – A Mixed Methods Study at a Private Medical College - RAHILA ALI; AZAM AFZAL; SARA SHAKIL; AMBER SULTAN; SHAZIA BABAR; JAVERIA REHMAN; MARIB GHULAM RASOOL MALIK; MOHAMMAD SHAHZAIB QADIR; SADAF KHAN; SANA SAEED (Journal of Advances in Medical Education and Professionalism)
Introduction: Case-based learning (CBL) is widely used in medical education to bridge theory and practice, but traditional methods often struggle to sustain student engagement and promote critical thinking. To address these challenges, Case-Based Integrated Learning (CBIL) was developed as a novel approach combining immersive and interactive learning techniques. This study aimed to evaluate the effectiveness of CBIL in enhancing engagement, critical thinking, and clinical reasoning among medical students, and explore faculty experiences regarding the pedagogy.Methods: An explanatory-sequential mixed-methods study was conducted in a private medical college in Pakistan. Quantitative data were collected through faculty (n=35) and student (n=122) evaluation surveys, and analyzed using descriptive statistics (mean, standard deviation, frequencies, and percentages). Qualitative data from focused group discussions (FGD) with faculty were analyzed thematically. A committee of clinical faculty and medical educationists developedfour CBIL prototypes. Faculty from various clinical specialties were trained on CBIL concepts and lesson planning, and the prototypes were used to develop engaging cases for subsequent sessions. Participants included faculty from diverse disciplines and students intheir third and fourth years of medical school.Results: The faculty considered the training very effective (overall satisfaction: 5.17±0.89 out of 6), with a vast majority being very satisfied with its relevance (86%, n=30) and structure (91%, n=32).Among students, 95% (n=116) were satisfied with the developed cases. Most of them were also satisfied with the clarity (92%, n=112) and applicability of the cases (96%, n=117). In FGD, facilitators expressed satisfaction with CBIL formats as it provided opportunities for engagement, in-depth analyses, and discussions.Conclusion: Interactive formats like CBIL can engage students by allowing opportunities for interaction, discussion, and peer-learning. This promotes improved understanding and critical thinking. Further exploration of the effectiveness and impacts on the learning of various interactive formats of case-based learning is essential.